Cholinergic Stimulation of Norepinephrine Release in Man: EVIDENCE OF A SYMPATHETIC POSTGANGLIONIC AXONAL LESION IN DIABETIC ADRENERGIC NEUROPATHY - Leveston, Steven A. (1979)
Amplification of endogenous cholinergic activity—produced by the intravenous injection of edrophonium, an acetylcholinesterase inhibitor which does not enter the central nervous system, into normal subjects—resulted in significant and briefly sustained increments in the plasma concentrations of norepinephrine (153±15−234±29 pg/ml, P < 0.01) and epinephrine (16±3−34±5 pg/ml, P < 0.01) measured with a single-isotope derivative method. These increments were not attributable to reflex responses to hemodynamic changes and similar increments in plasma norepinephrine occurred in adrenalectomized (epinephrine deficient) patients. Thus, cholinergic activation results in direct stimulation of sympathetic postganglionic neurons, with augmented norepinephrine release, and of the adrenal medullae, with augmented epinephrine release, in man. Four diabetic patients with hypoadrenergic postural hypotension exhibited blunted sympathetic postganglionic neural responses, and normal adrenomedullary responses, to cholinergic stimulation (and to standing) indicative of the presence of a sympathetic postganglionic axonal lesion in diabetic adrenergic neuropathy. Nondiabetic patients with hypoadrenergic postural hypotension due to documented or probable central nervous system lesions exhibited normal responses to cholinergic stimulation produced in this fashion demonstrating the presence of intact sympathetic postganglionic neurons and adrenal medullae in these patients and providing further support for the conceptual soundness of this approach to the study of human adrenergic physiology and pathophysiology.